Use of antiretroviral treatment among people living with HIV in Australia between 1997 and 2012 - Power, J.; Lyons, A.; Brown, Graham; Dowsett, G.; Lucke, J. (Routledge, 2017)
Â© 2016 Informa UK Limited, trading as Taylor & Francis Group. Current international targets aim for 90% of people diagnosed with HIV to be on antiretroviral treatment (ART). This paper aims to identify sociodemographic and attitudinal factors associated with ART non-use over time in three samples of Australian people living with HIV (PLHIV). Data for this paper were derived from an Australian cross-sectional survey of PLHIV that was repeated at three different time points: 1997, 2003, and 2012. There were approximately 1000 respondents to each survey (n = 3042 in total). The survey included approximately 250 items related broadly to health and well-being, ART use, and attitudes towards ART use. Univariate and multivariate logistic regression analyses were used. While the proportion of participants using ART increased between 1997 and 2012 (78.8â€“87.6%, p < .001), there was a decrease between 1997 and 2003 to 70.6% (p < .001). Factors linked to ART non-use remained steady over those 15 years. In all cohorts, people less likely to be using ART were younger and had a more recent diagnosis of HIV. In 2003 and 2012, people in full-time employment were less likely to be using ART, while those whose main source of income was a pension or social security were more likely to be using ART. Multivariate models showed that, at each time point, a belief in the health benefits of delayed ART uptake was associated with non-use. These findings suggest that there may be barriers to ART uptake that have persisted over time despite changes to clinical guidelines that now encourage early uptake.